The Enantioselective Dakin–West Reaction. (25th January 2016) - Wende, Raffael C.; Seitz, Alexander; Niedek, Dominik; Schuler, Sören M. M.; Hofmann, Christine; Becker, Jonathan; Schreiner, Peter R.
Abstract: Here we report the development of the first enantioselective Dakin–West reaction, yielding α‐acetamido methylketones with up to 58 % ee with good yields. Two of the obtained products were recrystallized once to achieve up to 84 % ee . The employed methylimidazole‐containing oligopeptides catalyze both the acetylation of the azlactone intermediate and the terminal enantioselective decarboxylative protonation. We propose a dispersion‐controlled reaction path that determines the asymmetric reprotonation of the intermediate enolate after the decarboxylation.